Green Consumer’s Paradox - Acosta Bahena, Almeirim Isabel (Mercados y Negocios, 2024)
The paper aims to analyze the contradiction between green consumers’ behavior and green technology foods offered to them. An analysis of papers from different authors showed that green consumers are willing to make conscious food consumption. However, factors like price, knowledge about the green cause, consumer income, reference groups, shopping convenience, and food availability influence their final consumption. Collective intelligence is a solution for green consumers to make better decisions: it also involves challenges, ethical considerations, and avoiding political influences on shared information. In conclusion, governments and food producers must do a lot to ensure green consumers have enough tools to make informed and sustainable alimentary decisions.